Radio-Tracer Studies of Self Diffusion of Bivalent and Trivalent Ions in Agar Gel - Gupta R.P. (My University, 2025)
The self-diffusion coefficients of Cs+, Ca++, Sr++, Co++, Cd++ and Cr+++ ions were studied at various concentrations in agar gel media at 25 °C by “zone” diffusion technique. The results have been compared with the values obtained by other methods in aqueous solution. The study reveals that at lower concentrations the experimental values of self-diffusion coefficients of all the ions agree with the theoretical values obtained from the Gosting and Harned equation derived from the Onsager-Fuoss-theory of diffusion. However, a divergence between the theoretical and experimental values at higher concentrations has been explained in the light of the Onsager-Fuoss-theory wherein the change in the viscosity, dielectric relaxation, self energy of the ions and the ion-dipole interaction have been accounted for. The results have also been discussed in the light of gel interaction and partial desolvation effect of the agar gel on the hydrated ionic radii. © 1974, Walter de Gruyter. All rights reserved.